Preparation method of HA / g-C3N4 composite material with both heavy metal ion adsorption and visible light catalytic performance

By preparing HA/g-C3N4 composite materials, the problem of easy agglomeration and poor adsorption capacity of g-C3N4 materials in the prior art is solved, and efficient heavy metal ion adsorption and visible photocatalytic degradation effects are achieved, simplifying the preparation process and reducing production cost.

CN112661229BActive Publication Date: 2025-01-14NANJING HEZHI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202011354586.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-11-27
Publication Date
2025-01-14
Estimated Expiration
2040-11-27

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently remove heavy metal ions and visible photocatalytic degradation dyes in printing and dyeing wastewater at the same time. The g-C3N4 material has problems such as easy agglomeration, low efficiency, difficult separation, high production cost and poor adsorption capacity, and lacks effective synergistic materials. .

Method used

Using HA/g-C3N4 composite material, the composite material is prepared by ultrasonic dispersion and calcination of melamine and thiourea with HA to form a composite material with heavy metal ion adsorption and visible photocatalytic properties, and the process parameters are adjusted to control the morphology, size and composition.

Benefits of technology

It realizes efficient adsorption of heavy metal ions and visible photocatalytic degradation dyes, improves the adsorption rate and photocatalytic efficiency of g-C3N4, simplifies the preparation process, reduces production costs, and improves the stability and yield of materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112661229B_ABST
    Figure CN112661229B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a hydroxyapatite-modified carbon nitride (HA / g-C3N4) composite material having both heavy metal ion adsorption and visible light catalytic performance, and the steps are as follows: dissolving melamine and thiourea in deionized water, stirring evenly, then adding HA for ultrasonic dispersion, transferring the resulting solution to a reactor for reaction at 180°C for 12 hours, cooling to room temperature and filtering, drying the filter cake to obtain a HA / g-C3N4 composite material precursor; grinding the precursor evenly in an agate mortar, placing the ground powder in a crucible, and calcining to obtain a HA / g-C3N4 composite material. The HA / g-C3N4 composite material prepared by the method has the advantages of simple and rapid preparation process, easy operation, environmental protection, large product yield, simple post-processing, and controllable product morphology, size and composition, etc., especially in the field of heavy metal ion adsorption and visible light degradation of pollutants, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite material preparation and application, and specifically relates to a HA / g-C3N4 composite material having both heavy metal ion adsorption and visible light catalytic performance, and a preparation method and application thereof. Background Art

[0002] The composition of printing and dyeing wastewater is complex. In addition to residual dyes, it also contains aromatic organic compounds and heavy metal elements such as copper, chromium, and cadmium. They enter organisms through the food chain, seriously endangering human life and health, and are an important source of water pollution. In response to this problem, among the various treatment methods proposed by many researchers, visible light photocatalytic degradation technology has attracted widespread attention due to its significant advantages such as non-toxicity, energy saving, and high efficiency in treating aromatic organic dyes discharged by the printing and dyeing industry. As for the removal of heavy metal ions, the most widely used is the adsorption technology with low cost, convenient operation, and good treatment effect, among which the selection and application of adsorbents are the key to adsorption technology.

[0003] g-C3N4 is an emerging non-metallic catalyst. Although g-C3N4 material was reported in 1930, it was not until 2006 that researchers used g-C3N4 as a catalyst, especially in the field of visible light catalysis. As a kind of inorganic material, HA has a very outstanding advantage in adsorbent materials due to its unique spatial structure type and related active group structure. On the other hand, HA has the advantages of wide source, low cost and no secondary pollution, and is widely used to adsorb heavy metal ions in water. Therefore, if g-C3N4 can be physically or chemically combined with HA and applied to water pollution control, it can not only adsorb heavy metal ions in sewage but also degrade organic pollutants such as dyes in water under visible light. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a HA / g-C3N4 composite material having both heavy metal ion adsorption and visible light catalytic performance and a preparation method thereof. The preparation process is simple, fast and easy to operate.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A method for preparing a HA / g-C3N4 composite material having both heavy metal ion adsorption and visible light catalytic performance, the steps are as follows:

[0007] (1) Preparation of HA / g-C3N4 composite material precursor: Melamine and thiourea were dissolved in deionized water and stirred evenly, and then HA was added for ultrasonic dispersion. The resulting solution was transferred to a reactor and reacted at 180°C for 12 h. After cooling to room temperature, it was filtered and the filter cake was dried to obtain a HA / g-C3N4 composite material precursor.

[0008] (2) Preparation of HA / g-C3N4 composite material: The HA / g-C3N4 composite material precursor prepared in step (1) is placed in an agate mortar and ground evenly. The ground powder is placed in a crucible and calcined to obtain a HA / g-C3N4 composite material.

[0009] Furthermore, in step (1), the molar ratio of melamine to thiourea is 1:0.05 to 1:0.5.

[0010] Furthermore, in the step (1), the mass ratio of HA to melamine is 5% to 50%, and the particle size of the added HA is 100nm to 2000nm.

[0011] Furthermore, the drying temperature in step (1) is 80° C. and the drying time is 6 hours.

[0012] Furthermore, in step (2), the calcination temperature is 520° C. and the calcination time is 1 to 8 hours.

[0013] The HA / g-C3N4 composite material with both heavy metal ion adsorption and visible light catalytic performance is prepared by the preparation method of the present invention.

[0014] Beneficial effects of the present invention:

[0015] (1) The preparation process is simple, fast and easy to operate.

[0016] (2) The product yield is large and post-processing is simple, and it only needs to be ground to the required particle size.

[0017] (3) The morphology, size and composition of the product are controllable. By adjusting the process parameters of the synthesis reaction such as the molar ratio of melamine to thiourea in the raw materials, the HA content and the calcination time, a HA / g-C3N4 composite material with controllable morphology, size and content can be obtained.

[0018] (4) The original layered structure of g-C3N4 materials prepared by traditional thermal polymerization is prone to agglomeration, resulting in a low specific surface area of ​​the catalyst and poor adsorption and capture ability for pollutants. In addition, monomer g-C3N4 also has problems such as short lifetime of photogenerated carriers and high recombination rate of electron-hole pairs, which greatly limits the practical application of g-C3N4 photocatalytic materials in the field of environmental protection. HA is an adsorption material and photocatalytic material with a simple synthesis process, which has been used in the treatment of organic wastewater. Although the existing g-C3N4 modification process can partially solve the defects of g-C3N4, the material itself still has problems such as easy agglomeration, low efficiency, difficult separation, high production cost and poor adsorption capacity. There is a synergistic effect between g-C3N4 and HAP. HAP can significantly improve the adsorption rate of g-C3N4 for heavy metal ions and extend the lifetime of photoelectrons, thereby improving its photocatalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is the X-ray diffraction pattern of the HA / g-C3N4 composite material prepared in Example 1 of the present invention, the g-C3N4 prepared in Comparative Example 1, and the HA prepared in Comparative Example 2.

[0020] Figure 2 The Pb content of the HA / g-C3N4 composite material prepared in Example 1 of the present invention, the g-C3N4 prepared in Comparative Example 1, and the HA prepared in Comparative Example 2 is 2+ Adsorption diagram.

[0021] Figure 3 It is a visible light catalytic image of the HA / g-C3N4 composite material prepared in Example 1 of the present invention, the g-C3N4 prepared in Comparative Example 1, and the HA prepared in Comparative Example 2. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention, and those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.

[0023] Example 1

[0024] The preparation method of the HA / g-C3N4 composite material having both heavy metal ion adsorption and visible light catalytic performance in this embodiment comprises the following steps:

[0025] (1) Preparation of HA / g-C3N4 composite material precursor: Melamine and thiourea were dissolved in deionized water at a molar ratio of 1:0.05 and stirred evenly. HA (HA accounted for 5% of melamine by mass and had a particle size of 200 nm) was added to the solution and dispersed by ultrasonic. The solution was then transferred to a reactor and reacted at 180°C for 12 h. After cooling to room temperature, the mixture was filtered and the filter cake was dried at 80°C for 6 h to obtain a HA / g-C3N4 composite material precursor.

[0026] (2) Preparation of HA / g-C3N4 composite material: The precursor of the HA / g-C3N4 composite material obtained above was fully and evenly ground in an agate mortar. The ground powder was placed in a crucible and calcined at 520°C for 1 h to obtain a HA / g-C3N4 composite material.

[0027] Example 2

[0028] The preparation method of the HA / g-C3N4 composite material having both heavy metal ion adsorption and visible light catalytic performance in this embodiment comprises the following steps:

[0029] (1) Preparation of HA / g-C3N4 composite material precursor: Melamine and thiourea were dissolved in deionized water at a molar ratio of 1:0.1 and stirred evenly. HA (HA accounted for 50% of melamine by mass and had a particle size of about 2000 nm) was added to the above solution and dispersed by ultrasonic. The above solution was then transferred to a reactor and reacted at 180°C for 12 h. After cooling to room temperature, the mixture was filtered and the filter cake was dried at 80°C for 6 h to obtain a HA / g-C3N4 composite material precursor.

[0030] (2) Preparation of HA / g-C3N4 composite material: The precursor of the HA / g-C3N4 composite material obtained above was fully and evenly ground in an agate mortar. The ground powder was placed in a crucible and calcined at 520°C for 8 h to obtain a HA / g-C3N4 composite material.

[0031] Example 3

[0032] The preparation method of the HA / g-C3N4 composite material having both heavy metal ion adsorption and visible light catalytic performance in this embodiment comprises the following steps:

[0033] (1) Preparation of HA / g-C3N4 composite material precursor: Melamine and thiourea were dissolved in deionized water at a molar ratio of 1:0.5 and stirred evenly. HA (HA accounted for 25% of melamine by mass and had a particle size of about 1000 nm) was added to the above solution and dispersed by ultrasonic. The above solution was then transferred to a reactor and reacted at 180°C for 12 h. After cooling to room temperature, the mixture was filtered and the filter cake was dried at 80°C for 6 h to obtain a HA / g-C3N4 composite material precursor.

[0034] (2) Preparation of HA / g-C3N4 composite material: The precursor of the HA / g-C3N4 composite material obtained above was fully and evenly ground in an agate mortar. The ground powder was placed in a crucible and calcined at 520°C for 4 h to obtain a HA / g-C3N4 composite material.

[0035] Comparative Example 1 (without adding HA)

[0036] On the basis of Example 1, without adding HA, melamine and thiourea were dissolved in deionized water at a ratio of 1:0.05 (molar ratio), stirred evenly, and then HA (HA accounted for 5% of the mass ratio of melamine) was added to the above solution for ultrasonic dispersion, and then the above solution was transferred to a reactor for reaction at 180°C for 12h, cooled to room temperature and filtered, and the obtained filter cake was dried at 80°C for 6h to obtain a precursor of g-C3N4. The above obtained precursor of g-C3N4 was fully and evenly ground in an agate mortar, and the ground powder was placed in a crucible and calcined at 520°C for 1h to obtain g-C3N4.

[0037] Comparative Example 2

[0038] The raw material HA is fully and evenly ground in an agate mortar, the ground powder is placed in a crucible, and calcined at 520° C. for 1 h to obtain calcined HA.

[0039] The HA / g-C3N4 composite material prepared in Example 1 was subjected to heavy metal ion adsorption and photocatalytic performance tests as follows:

[0040] (1) Adsorption experiment of heavy metal ions (taking Pb 2+For example: 0.10 g HA / g-C3N4 composite material (or pure g-C3N4) was accurately weighed and added to a series of 150 mL conical flasks, and 100 mL of Pb(NO3)2 solution with an initial concentration of 0.01 mol / L was added respectively. The mixture was placed in a constant temperature oscillator at r = 200 rpm and T = 35 °C for 60 min, 120 min, 180 min, 240 min, 300 min and 360 min, respectively, and the adsorption reaction was stopped. The mixture was filtered and the residual Pb in the solution was determined by complexometric titration. 2+ The equilibrium concentration of HA / g-C3N4 was calculated and the equilibrium adsorption capacity was calculated. The test results show that under the same adsorption conditions, compared with pure g-C3N4, HA / g-C3N4 composite materials have a higher adsorption capacity for Pb 2+ The adsorption rate increased by 80%.

[0041] (2) Visible light catalytic degradation of pollutants experiment:

[0042] The photocatalytic performance of the prepared HA / g-C3N4 composite material was tested as follows:

[0043] A 150 W xenon lamp was used as the light source (with a filter to filter out wavelengths less than 400 nm), and a 10 mg / L rhodamine B aqueous solution was used as the simulated waste liquid. First, the adsorption equilibrium was maintained in a dark room for 0.5 h. Samples were taken at regular intervals and centrifuged to obtain the clear liquid. The absorbance was then measured at a wavelength of 554 nm. The concentration of the solution was calculated, and the degradation rate of rhodamine B was calculated based on this.

[0044] The test results show that compared with pure g-C3N4, the degradation efficiency of HA / g-C3N4 composite materials for rhodamine B increased by about 70%. After five cycles of use, the degradation rate of pure g-C3N4 for rhodamine B dropped below 40%, while the HA / g-C3N4 composite material did not change much.

[0045] The heavy metal ion adsorption experiment and photocatalytic performance test showed that the HA / g-C3N4 composite material had a good photocatalytic performance. 2+ It has good adsorption effect and good visible light photocatalysis for rhodamine B. The introduction of HA greatly improves the heavy metal ion adsorption performance and photocatalytic activity of g-C3N4.

[0046] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. HA / g-C3N4 composites in Pb 2+ Application in adsorption and visible light catalysis, characterized by: Accurately weigh 0.10 g of HA / g-C3N4 composite material and add it to a series of 150 mL conical flasks, add 100 mL of Pb(NO3)2 solution with an initial concentration of 0.01 mol / L, place it in a constant temperature oscillator at r = 200 rpm and T = 35 °C, and stop the adsorption reaction at 60 min, 120 min, 180 min, 240 min, 300 min and 360 min, respectively. Filter and determine the residual Pb in the solution by complexometric titration 2+ The equilibrium concentration was calculated and the equilibrium adsorption capacity was calculated. The test results show that under the same adsorption conditions, compared with pure g-C3N4, HA / g-C3N4 composite materials have a higher adsorption capacity for Pb 2+ The adsorption rate increased by 80%; The photocatalytic performance of the prepared HA / g-C3N4 composite material was tested as follows: A 150 W xenon lamp was used as the light source, and a 10 mg / L Rhodamine B aqueous solution was used as the simulated waste liquid. First, the adsorption equilibrium was maintained in a dark room for 0.5 h, and a sample was taken at a certain interval. The clear solution was separated by centrifugation, and then the absorbance was measured at a wavelength of 554 nm. The concentration of the solution was calculated, and the degradation rate of Rhodamine B was calculated based on this. The test results show that compared with pure g-C3N4, the degradation efficiency of HA / g-C3N4 composite material on Rhodamine B is increased by 70%. After 5 cycles of use, the degradation rate of pure g-C3N4 on Rhodamine B dropped to below 40%, while the HA / g-C3N4 composite material did not change much. The preparation method of the HA / g-C3N4 composite material comprises the following steps: (1) Preparation of HA / g-C3N4 composite material precursor: Melamine and thiourea were dissolved in deionized water at a molar ratio of 1:0.05, stirred evenly, and then HA was added to the above solution for ultrasonic dispersion, wherein the mass ratio of HA to melamine was 5%, and its particle size was 200 nm; then the above solution was transferred to a reactor and reacted at 180°C for 12 hours, cooled to room temperature and filtered, and the obtained filter cake was dried at 80°C for 6 hours to obtain a precursor of HA / g-C3N4 composite material; the HA was hydroxyapatite; (2) Preparation of HA / g-C3N4 composite material: The precursor of the HA / g-C3N4 composite material obtained above was fully and evenly ground in an agate mortar. The ground powder was placed in a crucible and calcined at 520°C for 1 h to obtain a HA / g-C3N4 composite material.

Citation Information

Patent Citations

  • g-C3N4 / kaolinite composite photocatalyst and preparation method thereof

    CN106111174A

  • Preparation method of composite material capable of realizing high efficiency adsorption-photocatalysis degradation of antibiotics

    CN108786889A